Ascendino Leite: uma representação do ser leitor no Jornal Literário - Silva, Maria Célia Ribeiro da (2014)
The present research aims at investigating the anthology Sementes no Espaço (1938-1988): fragmentos de um Jornal Literário, by Ascendino Leite. Such literary work consists of two volumes, which were published, respectively, in 1988 and 1989. As to its theme, it focuses on the writer‟s inner universe, considering both his daily and literary life. Such approach considers Ascendino‟s representations as being a reader , and the way this condition contributed so as to reveal his tricks when representing literary life in a hybrid nature text, such as a Literary Journal. Besides, it also focuses on some personal and political matters, as well as on the author-function , and on the recognition, or not, of the name Ascendino, as a writer. In order to perform this research, the anthology Sementes no Espaço (1938-1988): fragmentos de um Jornal Literário was used. Such Literary work was organized by the writer, the author‟s personal file (notes, notebook, agenda, cards, pictures, part of the collection of his private library, letters), and texts, which were published in the journalistic sphere. Besides, we also made use of some friends‟ and writers‟ memories, aiming at reaching a representation of his image, both as an individual and as a reader. As to the theory, we based ourselves on Roger Chartier (1990; 1999a; 1999b) and on Michel de Certeau (2009), with the concepts of representation, practice, appropriation, and the notion of tactics (DE CERTEAU, 2009). Such concepts concern the actions performed by Ascendino, as a reader, so as to contribute to the formation of the Literary Journal and on the author-function, as explicited by Foucault (1992). As to Hébrard (2000) and Chartier (1990; 1999a; 1999b), they were our resource considering the notion of support. We also referred to Barthes (1984), Chartier (2007) and other authors for supporting some reflections concerning reading.